Supplier Selection Strategy And Manufacturing Flexibility: Impact Of Quality And Technology Roadmaps - Muhamad Jantan, Muhamad Jantan; Ndubisi, Nelson Oly; Loo , Cha Hing (Asian Academy of Management (AAM), 2006)
The study evaluates the relationship between technology, quality, cost and delivery performance-based, supplier selection strategies, and manufacturing flexibilities namely, product flexibility, launch flexibility, and volume flexibility. Moreover, the moderating impact of supplier management strategies, namely quality roadmap and technology roadmap on the above relationships were also explored. The data for the study was drawn from a sample of companies listed in the factory directory published by the Penang Development Corporation (PDC). A postal survey of 120 manufacturers provided a return of 92 usable responses. The results reveal that the selection of suppliers based on technological and quality performance positively affects all the three dimensions of manufacturing flexibility, with complementary effects of good technology and quality roadmaps. Technology and quality roadmaps act as predictors for product and volume flexibilities. However, when launch flexibility is the focus, both technology and quality roadmaps moderate the impact of supplier selection strategies. Details of the findings, theoretical and practical implications, and the research limitation are discussed.